ANALYSIS OF HEALTH WORKER AND PEER SUPPORT GROUP INFLUENCE ON ANTIRETROVIRAL (ARV) ADHERENCE AT DR. DJASAMEN SARAGIH GENERAL HOSPITAL, PEMATANGSIANTAR - Jakasmir Girsang; Tiarnida Nababan; Refi ikhtiari (Nurse and Holistic Care, 2026)
Background: The low success of antiretroviral (ARV) therapy at Dr. Djasamen Saragih Regional Hospital is reflected in the small number of People Living with HIV (PLHIV) who achieve viral load suppression. This problem is strongly suspected to be related to the low level of medication adherence. Objective: To analyze the effect of support from health workers and Peer Support Groups (PSGs) on ARV adherence at Dr. Djasamen Saragih Regional Hospital.Methods: This study used a cross-sectional design. The study population was all PLHIV, totaling 229 people, with a sample size of 71 people taken through a purposive sampling method. Data were analyzed bivariate and multivariate to determine the relationship between variables and the odds ratio of patient adherence.Results: Bivariate analysis showed a significant relationship between support from health workers (p=0.000) and peer support (p=0.001) on ARV adherence. The results of the multivariate analysis showed that support from healthcare workers was the dominant factor, where PLHIV who received such support had a 7.830 times greater chance of adherence than those who did not receive support. In addition, peer support increased the chance of adherence by 4.729 times for patients.Conclusion: External support, both from medical personnel and the peer social environment, significantly determined the adherence behavior of PLHIV in undergoing therapy. The management of Dr. Djasamen Saragih Regional General Hospital is advised to improve the communication competency of healthcare workers and strengthen strategic collaboration with peer communities in Pematangsiantar City to optimize patient therapy outcomes.